Identification of 2-(thiophen-2-yl)acetic Acid-Based Lead Compound for mPGES-1 Inhibition - Di Micco, Simone; Terracciano, Stefania; Ruggiero, Dafne; Potenza, Marianna; Vaccaro, Maria C.; Fischer, Katrin; Werz, Oliver; Bruno, Ines; Bifulco, Giuseppe (Frontiers in Chemistry, 2021)
We report the implementation of our in silico/synthesis pipeline by targeting the glutathione-dependent enzyme mPGES-1, a valuable macromolecular target in both cancer therapy and inflammation therapy. Specifically, by using a virtual fragment screening approach of aromatic bromides, straightforwardly modifiable by the Suzuki-Miyaura reaction, we identified 3-phenylpropanoic acid and 2-(thiophen-2-yl)acetic acid to be suitable chemical platforms to develop tighter mPGES-1 inhibitors. Among these, compounds 1c and 2c showed selective inhibitory activity against mPGES-1 in the low micromolar range in accordance with molecular modeling calculations. Moreover, 1c and 2c exhibited interesting IC50 values on A549 cell lines compared to CAY10526, selected as reference compound. The most promising compound 2c induced the cycle arrest in the G0/G1 phase at 24 h of exposure, whereas at 48 and 72 h, it caused an increase of subG0/G1 fraction, suggesting an apoptosis/necrosis effect.